PATIENTS WITH END-STAGE RENAL DISEASE ADMITTED TO THE INTENSIVE CARE UNIT: SYSTEMATIC REVIEW - Ma’bud, Tasia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: The prevalence and incidence of Chronic Kidney Disease (CKD), especially End-Stage Renal Disease (ESRD), are rising globally, primarily due to aging populations, hypertension, diabetes, and obesity. The prevalence of chronic kidney disease (CKD) in critically ill patients is incompletely documented. Aim: This study aims to determine the frequency of critical care unit visits among individuals with end-stage renal disease. Methods: This study demonstrated compliance with all requirements of the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 standards through self-comparison. The experts ensured the study's maximum contemporaneity. The search strategy involved examining publications published from 2013 to 2023. This was accomplished using various online reference databases, including Pubmed and SagePub. Only completed papers and publications were considered, while incomplete pieces and previously published works were excluded. Result: 1,662 and 1,212 articles were retrieved from PubMed and SagePub, respectively. In 2013, we collated 16 papers, including 11 from PubMed and 5 from SagePub, 4 of which met the research criteria. Conclusion: ICU patients frequently exhibit advanced kidney disease and elevated mortality rates.